Morphological and optical properties of hierarchical tubular VOPcPhO nanoflowers - Kamarundzaman, A.; Fakir, M.S.; Supangat, A.; Sulaiman, K.; Zulfiqar, H. (Elsevier, 2013)
In this study, the morphological and optical properties of hierarchical tubular vanadyl 2,9,16,23-tetraphenoxy-29H,31H-phthalocyanine (VOPcPhO) flower-like nanostructures were reported. VOPcPhO nanoflowers have been synthesised from the solution concentration of 5 mg/ml via the template-assisted method. Dissolution of template has led to the growth of micrometer-sized flowers that have nanoscale features that are tubular shaped with protruding tips. The tubulars are self-assembled during the formation of flower-like nanostructures. UV–vis spectrum of VOPcPhO nanoflower shows a wider absorption at Q-band as compared to thin film. The changes in Raman shift were also observed which indicate the improvement of nanostructures exhibited by VOPcPhO nanoflowers.